Risk Factors for the Development and Severe Course of Ventilator-Associated Tracheobronchitis in Patients with Prolonged Mechanical Ventilation - R. A. Ibadov; D. M. Sabirov; O. D. Eshonkhodjaev; S. Kh. Ibragimov; G. M. Azizova; T. B. Ugarova (Общая реаниматология, 2023)
Objective. Identification of risk factors for the development and severe course of ventilator-associated tracheobronchitis (VAT) in patients on prolonged mechanical ventilation (PMV).Methods. VAT incidence rate in the intensive care unit of Academician V. Vakhidov Republican Scientific and Practical Medical Center for Surgery for the period 2018–2022 was evaluated retrospectively in 724 patients who were on PMV (more than 48 h). Patients’ clinical and demographic characteristics were subjected to factor analysis. Mean age was 52.4±3.3 (18–81) years. VAT was diagnosed based on clinical signs (fever 38°C, leukocytosis 12 000 ctlls/ml, or leukopenia 4 000 cells/ml, purulent endotracheal secretions, or conversion to purulent), radiological (no progression of existing or emergence of new pulmonary infiltrates) and microbiological (polymorphonuclear lymphocytes with or without bacteria, moderate-to active growth of colonies of potentially pathogenic microorganisms) criteria. VAT prophylaxis was based on the use of bacterial filters and humidification of the respiratory gas; selective decontamination of the digestive tract; regulation of pressure in the tracheal cuff; sanitation of the oral cavity. Treatment of VAT included antimicrobial drugs administered i/v and/or inhalational, bronchodilators, expectorants and mucolytics.Results. VAT incidence rate decreased over time from 24.7% to 10.1% (χ²=9.52; P=0.003) with invariable practice of ventilator support. The incidence of the most severe VAT (hemorrhagic catarrhal purulent) also gradually decreased from 44.7% to 14.3% (χ²=4.53; P=0.034).The duration of PMV and ICU stay in patients with VAT gradually decreased from 202.1±6.15 h to 125.3±7.81 h (t=7.73; P<0.0001), and from 9.7±0.25 days to 6.6±0.3 days (t=7.94; P<0.0001), respectively. In patients with VAT (N=122), in contrast to patients without VAT (N=602), the incidence of concomitant COPD was higher — 22.9% vs 10.6%, respectively (P<0.001). Gram-negative flora was the leading cause for development of severe tracheobronchitis, including Acinetobacter spp. — in 24% of cases, Klebsiella pneumoniae — in 11.6%, Pseudomonas aeruginosa — in 13.0%, Esherichia coli — 10.6%. Less frequently were isolated Staphylococcus aureus — in 5.3%, Enterococcus spp. — in 2.2% and Candida fungi — in 17.0%. The following predictors of severe VAT were identified: age over 60 years (OR=2.28; 95% CI 1.0–4.9), SAPS II  40 scores (OR=5.9; 95% CI 2.6–13.8), duration of mechanical ventilation 144 h (OR=5.4; 95% CI 1.8–16.7) and the presence of malignant neoplasms (OR=2.83; 95% CI 1.2–6.9). Conclusion. Decrease in VAT incidence rates, reduced duration of mechanical ventilation and ICU stay are indicative of adequate VAT prevention and treatment strategies within the analyzed period. Factors associated with VAT development and predictors of severe VAT can be used for identification of high risk patients.